2022
DOI: 10.1002/pon.5913
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Dignity Therapy narratives among people with severe mental illness and people with cancer

Abstract: Objective To examine Dignity Therapy (DT) narratives in patients with severe mental illness (SMI) and a control group of cancer patients. Methods 12 patients with SMI (schizophrenia, bipolar disorders, sever personality disorders) and 12 patients with non‐advanced cancer individually participated to DT interviews. DT was tape‐recorded, transcribed verbatim and shaped into a narrative through a preliminary editing process. A session was dedicated to the final editing process along with the participant, with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Experimental group: Family-oriented DT, three sessions (N = 60) 2. Control group: attention control (N = 60) DT group: significantly greater reduction in existential distress and depression at week one, significantly greater improvement in spiritual well-being at week one and four of follow-up Xiao et al (2022) [ 106 ] China Lung cancer patient and family member (dyad) N = 45 dyads Patients 62.2% M Caregivers 55.6% F Age mean - Patients: 54.47 ± 8.94 - Caregivers: 48.27 ± 11.53 Qualitative analysis Main themes: Benefits of the intervention ( Alleviating psychosocial distress; Improving personal relationship; Increase confidence in recovery); Risks of the intervention ( Triggering sad feelings); Factors to enhance successful dignity-conserving care ( Professional knowledge and skills; Facilitators' characteristics; Appropriate intervention timeline; Support from the leaders; Brief and flexible procedure; Integrated with health education); Difficulties and barriers to the delivery of dignity-conserving care ( Physical symptoms; Underrecognition of psychosocial care; Workload and time consumption) PSYCHIATRY Solomita and Franza (2022) [ 107 ] Italy (Avellino) BD and MDD N = 10 F:M = 6:4 Mean age 53.88 ± 16.66 Duration of disease ≥ 3 years Stabilization phase Adequate cognitive abilities (Epitrack) Observation study Amelioration of perceived dignity (reduction of PDI scores), functioning (increasing of GAF scores) and symptom severity (reduction in BPRS mean scores) administer before and 15 days after DT Avery and Baez (2012) [ 108 ] USA MDD F 61 years old Case report Coping with bereavement (loss of job) Increasing sense of dignity, purpose and meaning and will to live Grassi et al (2022) [ 109 ] Italy 12 patients with oncologic diseases 12 patients with severe mental illnesses (SMI) Qualitative study Same themes among the two groups: "Meaning making", "Resources", "Legacy", "Dignity" “Stigma” in the SMI group “Injustice” in the cancer group Avery and Savitz (2011) [ <...…”
Section: Resultsmentioning
confidence: 99%
“…Experimental group: Family-oriented DT, three sessions (N = 60) 2. Control group: attention control (N = 60) DT group: significantly greater reduction in existential distress and depression at week one, significantly greater improvement in spiritual well-being at week one and four of follow-up Xiao et al (2022) [ 106 ] China Lung cancer patient and family member (dyad) N = 45 dyads Patients 62.2% M Caregivers 55.6% F Age mean - Patients: 54.47 ± 8.94 - Caregivers: 48.27 ± 11.53 Qualitative analysis Main themes: Benefits of the intervention ( Alleviating psychosocial distress; Improving personal relationship; Increase confidence in recovery); Risks of the intervention ( Triggering sad feelings); Factors to enhance successful dignity-conserving care ( Professional knowledge and skills; Facilitators' characteristics; Appropriate intervention timeline; Support from the leaders; Brief and flexible procedure; Integrated with health education); Difficulties and barriers to the delivery of dignity-conserving care ( Physical symptoms; Underrecognition of psychosocial care; Workload and time consumption) PSYCHIATRY Solomita and Franza (2022) [ 107 ] Italy (Avellino) BD and MDD N = 10 F:M = 6:4 Mean age 53.88 ± 16.66 Duration of disease ≥ 3 years Stabilization phase Adequate cognitive abilities (Epitrack) Observation study Amelioration of perceived dignity (reduction of PDI scores), functioning (increasing of GAF scores) and symptom severity (reduction in BPRS mean scores) administer before and 15 days after DT Avery and Baez (2012) [ 108 ] USA MDD F 61 years old Case report Coping with bereavement (loss of job) Increasing sense of dignity, purpose and meaning and will to live Grassi et al (2022) [ 109 ] Italy 12 patients with oncologic diseases 12 patients with severe mental illnesses (SMI) Qualitative study Same themes among the two groups: "Meaning making", "Resources", "Legacy", "Dignity" “Stigma” in the SMI group “Injustice” in the cancer group Avery and Savitz (2011) [ <...…”
Section: Resultsmentioning
confidence: 99%
“…29 On a similar note, Grassi et al found that avoiding stigma in caring for patients with mental disorders and cancer shows respect for their identity and enhances their self-confidence and human dignity. 30 Also, according to Healy et al and Deng et al, a reduction in the stigmatization of patients with mental illnesses and their families in clinical environments will preserve their dignity. 31,32 Another theme extracted from the data in the present study was the management of psychological tension.…”
Section: Discussionmentioning
confidence: 99%
“…We read the paper by Grassi et al 1 with great interest and it captured our attention as it demonstrates how Dignity Therapy (DT) has broadened its application to different clinical settings and populations beyond cancer and terminality. Grassi and colleagues' paper was the basis for the authors' reflection on DT's trajectory over time, through the existing evidence, and across different populations experiencing suffering.…”
Section: Dear Editormentioning
confidence: 99%
“…15 In conclusion -looking at the past, the present and most importantly to DT's future -we believe the inner strength DT holds, resides in its capacity to find each patient's personhood beyond patienthood and still conscientious that personhood is soluble in patienthood. Additionally, DT focuses on reinforcing a continued sense of worth within a framework that is supportive, nurturing and accessible and, therefore, applicable not only for those facing impending death but also for people living with their illnesses and facing their unique suffering, in search for support, like Grassi and his collaborators 1 have also shown and thus, opened a new door.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation